Health Promotion For Stunting Prevention At The Simpang Pandan Health Center, Tanjung Jabung East - M. Ridwan; Usi Lanita; Nur Annisa (CV. AFDIFAL MAJU BERKAH, 2024)
The health promotion program is an essential program at the Public health center. Overcoming stunting at the Simpang Pandan Health Center is a problem for the community and health centers in an effort to prevent or counteract it. The purpose of this study is to find out the Implementation of the Health Promotion Program at the Simpang Pandan Health Center in Lokus Stunting Village 2020. This study used a qualitative method with a case study design. Data collection through in-depth interviews and document review. There were 12 informants in the study selected using a purposive sampling technique. The Puskesmas in handling stunting cases use a health promotion strategy by advocating for village heads to support through the village budget in preventing and overcoming stunting. The partnership with the PKK driving team and universities is an effort to accelerate education for the community and efforts to tackle stunting by providing additional food for those affected by stunting. Health promotion strategies can support cross-sectoral collaboration in supporting stunting prevention and control programs at the Public health center.